Controllable nearly zero thermal expansion behavior in Mn3Zn1−xCrxN (0 ≤ x ≤ 0.20) compounds. (15th March 2019) - Sun, Ying; Yuan, Xiuliang; Tian, Xingbin; Zhao, Suyang; Wu, Meimei; Wang, Zhihao; Hu, Pengwei; Wang, Cong
Abstract: Nearly zero thermal expansion (NZTE) behavior of Mn3 ZnN is broadened to a wider temperature range from 25 K to 150 K by Cr doping at Zn site. X-ray diffraction shows that the broadened NZTE behavior is closely related to a cubic phase (C2) below magnetic transition temperature (TN ). Magnetic investigations indicate that additional ferromagnetic interactions appear after Cr doping. The possible existence of the nearest Mn-Cr exchange interactions and change of local binding environment may be responsible for the stabilization of the special non-collinear magnetic configuration and thus the broadened NZTE behavior from TN to a very low temperature. Graphical abstract: Unlabelled Image